Ответы и объяснения

Лучший Ответ!
  • Bernard14
  • почетный грамотей
2013-12-29T14:42:42+00:00
 \sqrt{48}-13 \sqrt{ \frac{12}{25}}+ \sqrt{4 \frac{8}{25}   }  = 4\sqrt{3} - \frac{13*2}{5} \sqrt{3}+   \frac{6}{5} \sqrt{3} = \frac{ \sqrt{3} }{5} (20-26+6)=0



 ( \sqrt{11+6 \sqrt{2}}- \sqrt{11- 6\sqrt{2}  } )^{2} =11+6 \sqrt{2}-2 \sqrt{121-72}+11-6 \sqrt{2}   =22-14=8
Сейчас поправлю!
lfdfq
Спасибо что подсказали
поправь пожалуйста leonid bychkov
уже
2013-12-29T14:44:01+00:00

√(16*3)-13√(4*3/25)+√(108/25)=4√3-26/5√3+√4,32=4√3-5,2√3+1,2√3=0

Вроде так.